Sectarian Interpretations of the Bhagavad Gītā (Pursuits: A Journal of English Studies, 2022)
This research article deals with the sectarian commentaries of the Bhagavad Gītā. The study has its relevance to understand the text from the point of view of its orthodox sectarian interpretations. The article addresses on the research problem concerning to the uniformity of the message of the Gītā outlined by its jñāna and bhakti interpretations. The research approach (methodology) adopted for this study is the review-based analysis of the orthodox jñāna and bhakti interpretations of the text. The study has included the interpretations of Sankarācārya, Ramanujācārya, Madhvācārya, Vallabhācārya, Nimbarkācārya and Prabhupada as they represent the leading orthodox commentators of the Gītā. The study discloses that not all the above commentators of the Gītā are unanimous in revealing the concrete and undisputed message of the text. Instead, they interpret the text according to their own philosophy and find in the scripture the essential source of their own teachings.